2011
DOI: 10.1007/s10535-011-0161-0
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of P5CS gene in chickpea enhances salt tolerance without affecting yield

Abstract: Vigna Δ 1 -pyrroline-5-carboxylate synthetase (P5CS) cDNA was transferred to chickpea (Cicer arietinum L.) cultivar Annigeri via Agrobacterium tumefaciens mediated transformation. Following selection on hygromycin and regeneration, 60 hygromycin-resistant plants were recovered. Southern blot analysis of five fertile independent lines of T0 and T1 generation revealed single and multiple insertions of the transgene. RT-PCR and Western blot analysis of T0 and T1 progeny demonstrated that the P5CS gene is expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Transgenic chickpea overexpressing P5CSF129A had increased proline accumulation, and root biomass of transgenic plants increased under both salt and drought stress conditions. The authors speculated that proline may play an indirect role in increasing root biomass in the transgenic plants under stress conditions [56]. Additionally, a study shows that increases in chlorophyll and carotenoid levels increase salt tolerance and biomass in transgenic sweetpotato [57].…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic chickpea overexpressing P5CSF129A had increased proline accumulation, and root biomass of transgenic plants increased under both salt and drought stress conditions. The authors speculated that proline may play an indirect role in increasing root biomass in the transgenic plants under stress conditions [56]. Additionally, a study shows that increases in chlorophyll and carotenoid levels increase salt tolerance and biomass in transgenic sweetpotato [57].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study showed that the expression of P5CS transgene resulted in the overproduction of the P5CS enzyme in transgenic chickpea plants and an increase in proline accumulation. The accumulation of osmoprotectants may increase tolerance to osmotic stress and sodium toxicity (Ghanti et al, 2011). Overexpression of P5CS also increased stress tolerance of transgenic potato, rice, wheat, sweet sorghum, and sugarcane (Anoop and Gupta, 2003; Su and Wu, 2004; Hmida-Sayari et al, 2005; Vendruscolo et al, 2007; Su et al, 2011; Guerzoni et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Increased proline production and enhanced tolerance to multiple stresses have been reported in several transgenic plants, including potato ( Solanum tuberosum ) (Hmida-Sayari et al 2005), Arabidopsis (Chen et al 2013), chickpea ( Cicer arietinum ) (Ghanti et al 2011), and wheat ( Triticum aestivum ) (Vendruscolo et al 2007). The LhSorP5CS gene that we cloned in the present study is therefore also a candidate gene for future transgenic research in lily.…”
Section: Discussionmentioning
confidence: 99%